On executives of financial institutions as outside directors - Booth, James R; Deli, Daniel N (Journal of Corporate Finance, 1999)
We find that the presence of commercial bankers on the board is positively related to aggregate firm debt. Separating by type of debt, the presence of commercial bankers on the board is positively related to short-term, long-term, and total bank debt. We also find that while the presence of unaffiliated commercial bankers on the board is positively related to bank borrowing, the presence of affiliated commercial bankers on the board is not. The results are consistent with the theory that commercial bankers supply bank debt market expertise, but not with the theory that they sit on boards to monitor lending relationships.